2016
DOI: 10.1371/journal.pone.0164804
|View full text |Cite
|
Sign up to set email alerts
|

LIM-Only Protein 4 (LMO4) and LIM Domain Binding Protein 1 (LDB1) Promote Growth and Metastasis of Human Head and Neck Cancer (LMO4 and LDB1 in Head and Neck Cancer)

Abstract: Squamous cell carcinoma of the head and neck (HNSCC) accounts for more than 300,000 deaths worldwide per year as a consequence of tumor cell invasion of adjacent structures or metastasis. LIM-only protein 4 (LMO4) and LIM-domain binding protein 1 (LDB1), two directly interacting transcriptional adaptors that have important roles in normal epithelial cell differentiation, have been associated with increased metastasis, decreased differentiation, and shortened survival in carcinoma of the breast. Here, we implic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 63 publications
0
19
0
Order By: Relevance
“…As summarized in the Appendix Table, CRISPR/Cas9 has been used to knock out several genes in several HNC cell lines. Those attempts confirm the involvements of fibronectin and LDB1 for cancer cell and invasiveness (Wang et al 2015; Simonik et al 2016) and identify novel therapeutic targets such as p75NTR and MUL1-HSPA5 axis (Huang et al 2017; Kim et al 2018). However, CRISPR may provide greater breakthroughs in treating HNC.…”
Section: Applications Of Genome Editing Techniques In the Oral And Crmentioning
confidence: 68%
“…As summarized in the Appendix Table, CRISPR/Cas9 has been used to knock out several genes in several HNC cell lines. Those attempts confirm the involvements of fibronectin and LDB1 for cancer cell and invasiveness (Wang et al 2015; Simonik et al 2016) and identify novel therapeutic targets such as p75NTR and MUL1-HSPA5 axis (Huang et al 2017; Kim et al 2018). However, CRISPR may provide greater breakthroughs in treating HNC.…”
Section: Applications Of Genome Editing Techniques In the Oral And Crmentioning
confidence: 68%
“…Deletion of LMO4 impairs Ldb1 and SLK recruitment in migratory cells [24]. LMO4 is closely related to the occurrence of many malignant tumors, such as pancreatic cancer, non-small cell lung cancer, and head and neck cancer [27,28], and can affect the differentiation of T cells, leading to acute leukemia [29].…”
Section: Discussionmentioning
confidence: 99%
“…LMO4 functioned as an oncogene in diverse cancers, and high expression of LMO4 was linked to poor prognosis and low survival. 29 , 30 In mechanism, LMO4 interacted with proteins involved, among else, in tumorigenesis, such as P53. 31 Besides, a previous study demonstrated that LMO4 was targeted by miR-139-5p, and circRNA-BACH2 facilitated PTC deterioration by activating the expression of LMO4 by targeting miR-139-5p.…”
Section: Discussionmentioning
confidence: 99%